Orang Tua Peduli Gizi Balita di Masa Pandemi - Evanny Indah Manurung; Martina Pakpahan; Eva Chris Veronica Gultom; Deborah Siregar; Peggy S. Tahulending (Universitas Malahayati Lampung, 2022)
ABSTRAK Konsumsi makanan berdampak langsung pada status gizi. Konsumsi yang tidak memenuhi standar gizi dapat menimbulkan masalah gizi terutama pada bayi dan balita, seperti, stunting, underweight, dan gagal tumbuh. Pemenuhan gizi yang adekuat menunjang pertumbuhan bayi dan balita sesuai tumbuh dan kembangnya. Peningkatan pengetahuan terkait gizi balita menjadi hal penting yang dapat membantu pencegahan masalah gizi balita. Kegiatan Pengabdian kepada Masyarakat (PkM) dalam bentuk webinar, dilaksanakan pada hari Jumat, 8 April 2022, pukul 10.00-12.00 WIB. Webinar menggunakan platform zoom dalam bentuk edukasi mengenai masalah gizi balita dan pemberian nutrisi yang baik untuk balita. Kegiatan bertujuan untuk meningkatkan pengetahuan orangtua mengenai kebutuh nutrisi balita dan gangguan nutrisi pada balita, yang kemudian diharapakan dapat mencegah resiko stunting. Peserta webinar sebanyak 66 orang, yaitu sebanyak 11 (16.7%) adalah laki-laki, 83.3% adalah perempuan, dan sebanyak 50 (75.8%) bekerja dan 16 (24.2%) tidak bekerja. Hasil pre-test (mean= 49) dan post-test (mean=64) menunjukkan adanya peningkatan pengetahuan sebanyak 15 poin. Sesi ceramah dan diskusi berlangsung dengan baik. Peserta antusias megikuti edukasi dan aktif mengajukan pertanyaan aplikatif terkait pemenuhan gizi balita sehari-hari. Peningkatan pengetahuan terkait kebutuhan dan permasalah gizi pada Balita, diharapkan dapat berkontribusi dalam mencegah kejadian stunting. Kata Kunci: Balita, Gizi, Pandemi, Stunting ABSTRACT Food consumption has a direct impact on nutritional status. Consumption that does not meet nutritional standards can cause nutritional problems, especially in infants and children under five, such as stunting, being underweight, and failure to thrive. Fulfillment of adequate nutrition supports the growth of children under five years according to their growth and development. Increasing knowledge related to toddler nutrition is an important thing that can help prevent nutritional problems for toddlers. Community Service Activities in the form of a webinar, held on Friday, April 8, 2022, 10:00-12:00 WIB. The webinar uses the zoom platform in the form of education about nutritional problems and the provision of good nutrition for children under five years. The activity aims to increase parents' knowledge about the nutritional needs and nutritional disorders in children under five years, which is then expected to prevent the risk of stunting. There were 66 participants in the webinar, of which 11 (16.7%) were male, 83.3% were female, 50 (75.8%) worked and 16 (24.2%) did not. The results of the pre-test (mean = 49) and post-test (mean = 64) showed an increase in knowledge by 15 points. The lecture and discussion sessions went well. Participants enthusiastically participated in the education and actively asked applicable questions related to the daily nutritional fulfillment of in children under five years, which is then expected to prevent the risk of stunting. There were 66 participants in the webinar, of which 11 (16.7%) were male, 83.3% were female, 50 (75.8%) worked and 16 (24.2%) did not. The results of the pre-test (mean = 49) and post-test (mean = 64) showed an increase in knowledge by 15 points. The lecture and discussion sessions went well. Participants enthusiastically participated in the education and actively asked applicable questions related to the daily nutritional fulfillment of Children Under Five Years. Increased knowledge related to nutritional needs and problems in children under five is expected to contribute to preventing stunting. Keywords: Children Under Five Years, Nutrition, Pandemic, Stunting